Heat-conducting adhesive for high-heat-conductivity double-sided tape and preparation method of heat-conducting adhesive
By using thermally conductive adhesives prepared by modified polyurethane, diamine nitrile rubber and acrylate, a heterocyclic network structure is formed, which solves the problem of low thermal conductivity of existing thermal tapes, significantly improves thermal conductivity and mechanical properties, and meets the heat dissipation needs of electronic equipment.
Patent Information
- Application Number
- CN202411399090.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-28
AI Technical Summary
The existing thermal tape has low thermal conductivity and poor physical properties, making it difficult to meet the strict heat dissipation needs of electronic equipment.
Modified polyurethane, diamine nitrile rubber and acrylate are used to produce a thermally conductive adhesive for high-thermal conductivity double-sided tape through reaction, forming a heterocyclic network structure to enhance thermal conductivity and mechanical properties.
It significantly improves the thermal conductivity and mechanical properties of thermally conductive adhesives, and can more effectively meet the heat dissipation needs of electronic equipment.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat-conducting material preparation, in particular to a heat-conducting adhesive for a high-heat-conducting double-sided tape and a preparation method thereof. Background Art
[0002] The development of science and technology and the demand of the market have made electronic devices increasingly develop in the direction of miniaturization, lightness and high efficiency. This compact device structure significantly improves the power density inside the device. The heat generated during operation is not easy to dissipate and is easy to quickly accumulate to form high temperature, which affects the stable operation and service life of the equipment. Therefore, a stable and effective heat dissipation method has become the key to the miniaturization of electronic equipment. In addition to the heat transfer of the heat dissipation device to the surrounding environment, the heat dissipation effect of electronic equipment is also closely related to the heat conduction inside the device. Thermal conductive tape fills the gap in heat conduction. It is used to fill and connect between the heat source device and the heat dissipation device to form a complete heat dissipation channel to ensure the normal operation of the equipment.
[0003] The thermal conductive tapes currently on the market generally have the disadvantages of low thermal conductivity and poor physical properties, which makes it difficult to meet the increasingly stringent heat dissipation requirements of electronic equipment. Therefore, the present invention studies and prepares a thermal conductive adhesive for double-sided tape with high thermal conductivity. Summary of the invention
[0004] The object of the present invention is to provide a thermally conductive adhesive for a high thermally conductive double-sided tape and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a thermally conductive adhesive for a high thermally conductive double-sided tape, comprising modified polyurethane, diamine nitrile rubber, acrylate and a curing agent; the modified polyurethane is prepared by reacting hydroxyheterocyclic pyrrole, polyether polyol and polymethylene isocyanate; the curing agent is toluene diisocyanate.
[0006] Preferably, the hydroxyheterocyclic pyrrole is prepared by reacting amino acid methyl ester, carboxylbenzylmercaptooxadiazole and sodium methoxide.
[0007] Preferably, the carboxybenzylmercaptooxadiazole is prepared by reacting 2-pyridinecarboxylic acid hydrazide, carbon disulfide and m-bromomethylbenzoic acid.
[0008] Preferably, the diamine nitrile rubber is prepared by reacting pentadecylphenol, decanediamine and paraformaldehyde to generate oxazine resin, which is then reacted with nitrile rubber.
[0009] Preferably, the thermally conductive adhesive for high thermal conductivity double-sided tape and the preparation method thereof include the following specific steps:
[0010] S1. 2-pyridinecarboxylic acid hydrazide, potassium hydroxide and methanol are mixed in a mass ratio of 7 to 8:5:100, stirred evenly and transferred to an ice bath, carbon disulfide of the same mass as 2-pyridinecarboxylic acid hydrazide is added dropwise at a rate of 1 to 3 ml / min, the temperature is raised to 60 to 70°C, the reaction is carried out for 3 to 6 hours, the mixture is rotary evaporated and dissolved in deionized water, the pH is adjusted to 4.8 to 5.2 with glacial acetic acid, and potassium hydroxide of 2 to 3 times the mass of 2-pyridinecarboxylic acid hydrazide and potassium hydroxide of the same mass as 2-pyridinecarboxylic acid hydrazide are added after filtration, and m-bromomethylbenzoic acid of 0.15 to 0.19 times the mass of 2-pyridinecarboxylic acid hydrazide is added after stirring evenly, the reaction is carried out at 400 to 800 rpm for 6 to 8 hours, the mixture is distilled under reduced pressure and the pH is adjusted to 2.8 to 3.2 with hydrochloric acid, the mixture is filtered and dried to obtain carboxybenzylmercaptooxadiazole;
[0011] S2. The hydroxyheterocyclic pyrrole body and methanol are mixed in a mass ratio of 1 to 3:20, stirred evenly, and a 20 to 30% sodium methoxide solution of 1 to 3 times the mass of the hydroxyheterocyclic pyrrole body is added, the temperature is raised to 70 to 80 ° C, refluxed for 8 to 10 hours, cooled to room temperature, and then rotary evaporated and adjusted to pH 2 to 3 with hydrochloric acid, and chromatographed by a 2:1 volume ratio of ether alcohol and polyethylene column to obtain hydroxyheterocyclic pyrrole;
[0012] S3. Mix hydroxyheterocyclic pyrrole and polyether polyol in a mass ratio of 1 to 3:40, heat to 100 to 110° C., vacuum dehydrate to a moisture content of 0.02 to 0.05%, cool to 40 to 50° C., add dibutyltin dilaurate in an amount of 0.01 to 0.02 times the mass of hydroxyheterocyclic pyrrole and polymethylene isocyanate in an amount of 1.4 to 1.8 times the mass of hydroxyheterocyclic pyrrole, heat to 75 to 85° C., keep warm for 4 to 6 hours, then add triethanolamine in an amount of 0.2 to 0.3 times the mass of hydroxyheterocyclic pyrrole, stir at 600 to 800 rpm for 20 to 40 minutes, and vacuum degas to obtain a modified polyurethane;
[0013] S4. Put the nitrile rubber into a double-roll mill, add plasticizer DOP, stearic acid, paraffin and oxazine resin for mixing at a temperature of 40 to 60 ° C, add accelerator TMTD after 3 to 5 minutes, continue mixing for 10 to 20 minutes, take out and let stand for 24 hours, and then place it in an extruder base granulation to obtain diamine nitrile rubber;
[0014] S5. Mix the modified polyurethane, diamine nitrile rubber, acrylate and curing agent toluene diisocyanate, raise the temperature to 180-220° C., stir evenly and react for 2-6 hours to obtain a thermally conductive adhesive for a high thermally conductive double-sided tape.
[0015] Preferably, in the above step S1., the preparation method of m-bromomethylbenzoic acid is: m-methylbenzoic acid, N-bromosuccinimide, benzoyl peroxide and carbon tetrachloride are mixed in a mass ratio of 10-13:18:0.2:150, refluxed for 6-8 hours, filtered and washed with carbon tetrachloride and deionized water for 3-5 times in sequence, and dried to obtain m-bromomethylbenzoic acid.
[0016] Preferably, in the above step S2., the preparation method of the hydroxyheterocyclic pyrrole blank is as follows: amino acid methyl ester, dichloromethane, 4-dimethylaminopyridine and EDC·HCl are mixed in a mass ratio of 0.1:3:0.18~0.2:0.28~0.3, and after stirring evenly, a dichloromethane solution of 2,4-dichlorophenylacetic acid with a mass fraction of 8~10% and a mass fraction of 20~30 times the mass of amino acid methyl ester is added dropwise at a rate of 1~3 ml / min, and after reacting for 16~20 hours, it is washed with a sodium bicarbonate solution with a mass fraction of 5% and deionized water for 3~5 times, dried with anhydrous sodium sulfate, and then filtered and concentrated to obtain a hydroxyheterocyclic pyrrole blank.
[0017] Preferably, in the above step S4., the preparation method of the oxazine resin is: add 0.4 to 0.5 times the mass of decanediamine of the m-pentadecylphenol to the m-pentadecylphenol at a rate of 1 to 3 ml / min, then add polyformaldehyde of the same mass as the m-pentadecylphenol, heat to 90 to 95° C., react for 2 to 4 hours, cool to 70 to 75° C., separate and wash with deionized water for 3 to 5 times, and vacuum dry to obtain the oxazine resin.
[0018] Preferably, in the above step S4., the mass ratio of nitrile rubber, plasticizer DOP, stearic acid, paraffin and oxazine resin is 100:10:1.2:1.2:4-7.
[0019] Preferably, in the above step S1., the mass ratio of modified polyurethane, diamine nitrile rubber, acrylate and curing agent toluene diisocyanate is 20-40:8-9:30-50:3.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] The thermally conductive adhesive for the high thermally conductive double-sided tape prepared by the present invention comprises modified polyurethane, diamine nitrile rubber and acrylate;
[0022] The modified polyurethane is prepared by the reaction of hydroxy heterocyclic pyrrole, polyether polyol and polymethylene isocyanate; the hydroxy heterocyclic pyrrole is prepared by the reaction of amino acid methyl ester, carboxybenzylmercapto oxadiazole and sodium methoxide; the carboxybenzylmercapto oxadiazole is prepared by the reaction of 2-pyridine carboxyhydrazide, carbon disulfide and m-bromomethylbenzoic acid; 2-pyridine carboxyhydrazide, carbon disulfide and m-bromomethylbenzoic acid react to form a long-chain carboxybenzylmercapto oxadiazole with a terminal carboxyl group and a heterocyclic structure, which is further reacted with amino acid methyl ester and sodium methoxide to form a hydroxy heterocyclic pyrrole with multiple heterocyclic rings, which is then reacted with polyether polyol and polymethylene isocyanate to prepare the modified polyurethane; a large number of heterocyclic rings are introduced into the polyurethane to form a side chain, and a heterocyclic network structure is formed in the adhesive, thereby enhancing thermal conductivity;
[0023] The diamine nitrile rubber is prepared by reacting pentadecylphenol, decanediamine and polyformaldehyde to generate oxazine resin, which is then reacted with nitrile rubber; benzoxazine is introduced into the nitrile rubber to further enhance the thermal conductivity, while the diamine nitrile rubber, modified polyurethane and acrylate are compounded and introduced into the network structure of the polyurethane through hydrogen bond connection, and are evenly dispersed in the adhesive, thereby enhancing the mechanical properties of the adhesive. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the thermally conductive adhesive for the high thermally conductive double-sided tape prepared in the examples and comparative examples as follows:
[0026] Thermal conductivity: After the high thermal conductivity double-sided tapes prepared in the examples and comparative examples were cured with a thermal conductive adhesive to form the same samples, thermal conductivity tests were performed using a QTM-710 rapid thermal conductivity meter in accordance with ASTM C1113-90.
[0027] Mechanical properties: The high thermal conductivity double-sided tapes prepared in the examples and comparative examples were subjected to tensile strength and elongation at break tests with reference to GB / T1040.
[0028] Example 1
[0029] S1. m-Toluic acid, N-bromosuccinimide, benzoyl peroxide and carbon tetrachloride were mixed in a mass ratio of 10:18:0.2:150, refluxed for 6 hours, filtered and washed with carbon tetrachloride and deionized water three times in sequence, and dried to obtain m-bromomethylbenzoic acid; 2-Pyridinecarboxylic acid hydrazide, potassium hydroxide and methanol were mixed in a mass ratio of 7:5:100, stirred evenly and transferred to an ice bath, and 2-Pyridinecarboxylic acid hydrazide of equal mass was added dropwise at a rate of 1 ml / min. Carbon disulfide, heated to 60°C, reacted for 3 hours, rotary evaporated and dissolved in deionized water, adjusted to pH 4.8 with glacial acetic acid, filtered, added with potassium hydroxide twice the mass of 2-pyridinecarboxylic acid hydrazide and potassium hydroxide of the same mass as 2-pyridinecarboxylic acid hydrazide, stirred evenly, added with m-bromomethylbenzoic acid 0.15 times the mass of 2-pyridinecarboxylic acid hydrazide, reacted at 400rpm for 6 hours, vacuum distilled and adjusted to pH 2.8 with hydrochloric acid, filtered and dried to obtain carboxybenzylthioxadiazole;
[0030] S2. The amino acid methyl ester, dichloromethane, 4-dimethylaminopyridine and EDC·HCl were mixed in a mass ratio of 0.1:3:0.18:0.28, stirred evenly, and then a dichloromethane solution of 2,4-dichlorophenylacetic acid with a mass fraction of 8% and 20 times the mass of the amino acid methyl ester was added dropwise at a rate of 1 ml / min. After reacting for 16 hours, the mixture was washed three times with a mass fraction of 5% sodium bicarbonate solution and deionized water, dried over anhydrous sodium sulfate, filtered and concentrated to obtain a hydroxyheterocyclic pyrrole blank; the hydroxyheterocyclic pyrrole blank was mixed with methanol in a mass ratio of 1:20, stirred evenly, and then a sodium methoxide solution with a mass fraction of 20% and 1 times the mass of the hydroxyheterocyclic pyrrole blank was added, the temperature was raised to 70°C, refluxed for 8 hours, cooled to room temperature, and then rotary evaporated and the pH was adjusted to 2 with hydrochloric acid, and the hydroxyheterocyclic pyrrole was obtained by chromatography on a 2:1 volume ratio of ether alcohol and a polyethylene column;
[0031] S3. The hydroxyheterocyclic pyrrole and the polyether polyol were mixed in a mass ratio of 1:40, heated to 100°C, vacuum dehydrated to a moisture content of 0.02%, cooled to 40°C, added with dibutyltin dilaurate 0.01 times the mass of the hydroxyheterocyclic pyrrole and polymethylene isocyanate 1.4 times the mass of the hydroxyheterocyclic pyrrole, heated to 75°C, kept warm for 4h, and then added with triethanolamine 0.2 times the mass of the hydroxyheterocyclic pyrrole, stirred at 600rpm for 20min, and vacuum degassed to obtain a modified polyurethane;
[0032] S4. 0.4 times the mass of decanediamine of m-pentadecylphenol was added dropwise to m-pentadecylphenol at a rate of 1 ml / min, and then the mass of paraformaldehyde of m-pentadecylphenol was added, the temperature was raised to 90°C, the reaction was continued for 2 hours, the temperature was lowered to 70°C, the liquid was separated and washed 3 times with deionized water, and the oxazine resin was obtained by vacuum drying; the nitrile rubber was placed in a double-roll mill, and plasticizer DOP, stearic acid, paraffin and oxazine resin were added for mixing, the nitrile rubber was placed in a double-roll mill, and the mass ratio of plasticizer DOP, stearic acid, paraffin and oxazine resin was 100:10:1.2:1.2:4, the temperature was 40°C, and the accelerator TMTD was added after 3 minutes, and the mixing was continued for 10 minutes. After being taken out and allowed to stand for 24 hours, it was placed in an extruder for granulation to obtain diamine nitrile rubber;
[0033] S5. The modified polyurethane, diamine nitrile rubber, acrylate and curing agent toluene diisocyanate are mixed in a mass ratio of 20:8:30:3, the temperature is raised to 180°C, and the mixture is stirred evenly for 2 hours to obtain a thermally conductive adhesive for a high thermally conductive double-sided tape.
[0034] Example 2
[0035] S1. m-Toluic acid, N-bromosuccinimide, benzoyl peroxide and carbon tetrachloride were mixed in a mass ratio of 12:18:0.2:150, refluxed for 7 hours, filtered and washed with carbon tetrachloride and deionized water 4 times in sequence, and dried to obtain m-bromomethylbenzoic acid; 2-Pyridinecarboxylic acid hydrazide, potassium hydroxide and methanol were mixed in a mass ratio of 7.5:5:100, stirred evenly and transferred to an ice bath, and 2-Pyridinecarboxylic acid hydrazide and other substances were added dropwise at a rate of 2 ml / min. amount of carbon disulfide, heated to 65°C, reacted for 4 hours, rotary evaporated and dissolved in deionized water, adjusted to pH 5 with glacial acetic acid, filtered, added with 2.5 times the mass of 2-pyridinecarboxylic acid hydrazide and potassium hydroxide of the same mass as 2-pyridinecarboxylic acid hydrazide, stirred evenly, added with 0.17 times the mass of 2-pyridinecarboxylic acid hydrazide, reacted at 600rpm for 7 hours, vacuum distilled, adjusted to pH 3 with hydrochloric acid, filtered and dried to obtain carboxybenzylthioxadiazole;
[0036] S2. The amino acid methyl ester, dichloromethane, 4-dimethylaminopyridine and EDC·HCl were mixed in a mass ratio of 0.1:3:0.19:0.29, stirred evenly, and a dichloromethane solution of 2,4-dichlorophenylacetic acid with a mass fraction of 9% and 25 times the mass of the amino acid methyl ester was added dropwise at a rate of 2 ml / min. After reacting for 18 hours, the mixture was washed four times with a mass fraction of 5% sodium bicarbonate solution and deionized water, dried with anhydrous sodium sulfate, filtered and concentrated to obtain a hydroxyheterocyclic pyrrole blank; the hydroxyheterocyclic pyrrole blank was mixed with methanol in a mass ratio of 2:20, stirred evenly, and then a 25% sodium methoxide solution with a mass fraction of 2 times the mass of the hydroxyheterocyclic pyrrole blank was added, the temperature was raised to 75°C, refluxed for 9 hours, cooled to room temperature, and then rotary evaporated and the pH was adjusted to 2.5 with hydrochloric acid, and hydroxyheterocyclic pyrrole was obtained by chromatography on a 2:1 volume ratio of ether alcohol and a polyethylene column;
[0037] S3. The hydroxyheterocyclic pyrrole and the polyether polyol were mixed in a mass ratio of 2:40, heated to 105°C, vacuum dehydrated to a moisture content of 0.04%, cooled to 45°C, added with 0.015 times the mass of dibutyltin dilaurate and 1.6 times the mass of hydroxyheterocyclic pyrrole polymethylene isocyanate, heated to 80°C, kept warm for 5h, and then added with 0.25 times the mass of hydroxyheterocyclic pyrrole triethanolamine, stirred at 700rpm for 30min, and vacuum degassed to obtain a modified polyurethane;
[0038] S4. 0.45 times the mass of decanediamine of m-pentadecylphenol was added dropwise to m-pentadecylphenol at a rate of 3 ml / min, and then the mass of paraformaldehyde of m-pentadecylphenol was added, the temperature was raised to 93 ° C, the reaction was continued for 3 hours, the temperature was lowered to 73 ° C, the liquid was separated and washed 4 times with deionized water, and the oxazine resin was obtained by vacuum drying; the nitrile rubber was placed in a double-roll mill, and plasticizer DOP, stearic acid, paraffin and oxazine resin were added for mixing, the nitrile rubber was placed in a double-roll mill, and the mass ratio of plasticizer DOP, stearic acid, paraffin and oxazine resin was 100:10:1.2:1.2:5.5, the temperature was 50 ° C, and the accelerator TMTD was added after 4 minutes, and the mixing was continued for 15 minutes. After taking out and standing for 24 hours, it was placed in an extruder for granulation to obtain diamine nitrile rubber;
[0039] S5. The modified polyurethane, diamine nitrile rubber, acrylate and curing agent toluene diisocyanate were mixed in a mass ratio of 30:8.5:40:3, the temperature was raised to 200°C, and the mixture was stirred evenly for 4 hours to obtain a thermally conductive adhesive for a high thermally conductive double-sided tape.
[0040] Example 3
[0041] S1. m-Toluic acid, N-bromosuccinimide, benzoyl peroxide and carbon tetrachloride were mixed in a mass ratio of 13:18:0.2:150, refluxed for 8 hours, filtered and washed with carbon tetrachloride and deionized water for 5 times, dried to obtain m-bromomethylbenzoic acid; 2-Pyridinecarboxylic acid hydrazide, potassium hydroxide and methanol were mixed in a mass ratio of 8:5:100, stirred evenly and transferred to an ice bath, and 2-Pyridinecarboxylic acid hydrazide of equal mass was added dropwise at a rate of 3 ml / min. Carbon disulfide, heated to 70°C, reacted for 6 hours, rotary evaporated and dissolved in deionized water, adjusted to pH 5.2 with glacial acetic acid, filtered, added with potassium hydroxide 3 times the mass of 2-pyridinecarboxylic acid hydrazide and potassium hydroxide of the same mass as 2-pyridinecarboxylic acid hydrazide, stirred evenly, added with m-bromomethylbenzoic acid 0.19 times the mass of 2-pyridinecarboxylic acid hydrazide, reacted at 800rpm for 8 hours, vacuum distilled and adjusted to pH 3.2 with hydrochloric acid, filtered and dried to obtain carboxybenzylthioxadiazole;
[0042] S2. The amino acid methyl ester, dichloromethane, 4-dimethylaminopyridine and EDC·HCl were mixed in a mass ratio of 0.1:3:0.2:0.3, stirred evenly, and a dichloromethane solution of 10% 2,4-dichlorophenylacetic acid, which was 30 times the mass of the amino acid methyl ester, was added dropwise at a rate of 1 to 3 ml / min. After reacting for 16 to 20 hours, the mixture was washed 5 times with a 5% sodium bicarbonate solution and deionized water, dried over anhydrous sodium sulfate, filtered and concentrated to obtain a hydroxyheterocyclic pyrrole blank; the hydroxyheterocyclic pyrrole blank was mixed with methanol in a mass ratio of 3:20, stirred evenly, and then a 30% sodium methoxide solution, which was 3 times the mass of the hydroxyheterocyclic pyrrole blank, was added, heated to 80°C, refluxed for 10 hours, cooled to room temperature, and then rotary evaporated and the pH was adjusted to 3 with hydrochloric acid, and hydroxyheterocyclic pyrrole was obtained by chromatography on a 2:1 volume ratio of ether alcohol and a polyethylene column;
[0043] S3. The hydroxyheterocyclic pyrrole and the polyether polyol were mixed in a mass ratio of 3:40, heated to 110°C, vacuum dehydrated to a moisture content of 0.05%, cooled to 50°C, added with 0.02 times the mass of dibutyltin dilaurate and 1.8 times the mass of polymethylene isocyanate of the hydroxyheterocyclic pyrrole, heated to 85°C, kept warm for 6h, and then added with 0.3 times the mass of triethanolamine of the hydroxyheterocyclic pyrrole, stirred at 800rpm for 40min, and vacuum degassed to obtain a modified polyurethane;
[0044] S4. Add 0.5 times the mass of decanediamine to the m-pentadecylphenol at a rate of 1 to 3 ml / min, then add the mass of paraformaldehyde of the m-pentadecylphenol, heat to 95°C, react for 4 hours, cool to 75°C, separate and wash 5 times with deionized water, and vacuum dry to obtain oxazine resin; put the nitrile rubber into a double-roll mill, add plasticizer DOP, stearic acid, paraffin and oxazine resin for mixing, put the nitrile rubber into a double-roll mill, add plasticizer DOP, stearic acid, paraffin and oxazine resin in a mass ratio of 100:10:1.2:1.2:7, the temperature is 60°C, add accelerator TMTD after 5 minutes, continue mixing for 20 minutes, take out and let stand for 24 hours, place in an extruder base granulation, and obtain diamine nitrile rubber;
[0045] S5. The modified polyurethane, diamine nitrile rubber, acrylate and curing agent toluene diisocyanate are mixed in a mass ratio of 40:9:50:3, the temperature is raised to 220°C, and the mixture is stirred evenly for 6 hours to obtain a thermally conductive adhesive for a high thermally conductive double-sided tape.
[0046] Comparative Example 1
[0047] The composition of Comparative Example 1 is the same as that of Example 2. The difference between the preparation method of the thermally conductive adhesive for the high thermally conductive double-sided tape and that of Example 2 is that the modified polyurethane is prepared by reacting polyether polyol and polymethylene isocyanate.
[0048] Comparative Example 2
[0049] The composition of Comparative Example 2 is the same as that of Example 2. The preparation method of the thermally conductive adhesive for high thermally conductive double-sided tape is different from that of Example 2 in that it only includes diamine nitrile rubber and acrylate.
[0050] Comparative Example 3
[0051] The composition of Comparative Example 3 is the same as that of Example 2. The preparation method of the thermally conductive adhesive for high thermally conductive double-sided tape is different from that of Example 2 in that it includes modified polyurethane, nitrile rubber and acrylate.
[0052] Comparative Example 4
[0053] The composition of Comparative Example 4 is the same as that of Example 2. The preparation method of the thermally conductive adhesive for high thermally conductive double-sided tape is different from that of Example 2 in that it only includes modified polyurethane and acrylate.
[0054] Effect example
[0055] Table 1 below shows the performance analysis results of the thermally conductive adhesive for high thermally conductive double-sided tapes prepared using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4:
[0056] Table 1
[0057] Thermal conductivity (W / m·K) Tensile strength(MPa) Elongation at break (%) Example 1 2.58 4.8 70 Example 2 2.63 4.9 69 Example 3 2.50 4.6 74 Comparative Example 1 1.99 4.0 65 Comparative Example 2 1.64 3.9 62 Comparative Example 3 2.16 3.2 57 Comparative Example 4 2.02 3.0 54
[0058] By comparing the experimental data of the examples and the comparative examples in Table 1, it can be clearly found that the thermally conductive adhesive for high thermal conductive double-sided tape prepared using Examples 1, 2, and 3 has excellent mechanical properties and thermal conductivity.
[0059] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 1, Comparative Example 2, it can be found that the hydroxyheterocyclic pyrrole prepared by the reaction of amino acid methyl ester, carboxybenzylmercapto oxadiazole and sodium methoxide reacts with polyether polyol and polymethylene isocyanate to prepare a modified polyurethane, 2-pyridinecarboxyhydrazide, carbon disulfide and m-bromomethylbenzoic acid react to form a long-chain carboxybenzylmercapto oxadiazole with a terminal carboxyl group and a heterocyclic structure, and then further reacts with amino acid methyl ester and sodium methoxide to form a hydroxyheterocyclic pyrrole with multiple heterocyclic rings, which is then reacted with polyether polyol and polymethylene isocyanate to prepare a modified polyurethane, a large number of heterocyclic rings are introduced into the polyurethane to form side chains, and a heterocyclic network structure is formed in the adhesive, thereby enhancing thermal conductivity.
[0060] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 3, Comparative Example 4, it can be found that after the reaction of pentadecylphenol, decanediamine and polyformaldehyde to form oxazine resin, the diamine nitrile rubber prepared by reacting with nitrile rubber, benzoxazine is introduced into the nitrile rubber to further enhance the thermal conductivity. At the same time, the diamine nitrile rubber, modified polyurethane and acrylate are compounded, connected by hydrogen bonds, introduced into the network structure of the polyurethane, and evenly dispersed in the adhesive, thereby enhancing the mechanical properties of the adhesive.
[0061] Obviously, the above embodiments are merely examples for clearly illustrating the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. However, these obvious changes or modifications derived from the spirit of the present invention are still within the scope of protection of the present invention.
Claims
1. A thermally conductive adhesive for a high thermally conductive double-sided tape, characterized in that: The invention comprises modified polyurethane, diamine nitrile rubber, acrylate and curing agent; the modified polyurethane is prepared by reaction of hydroxy heterocyclic pyrrole, polyether polyol and polymethylene isocyanate; and the curing agent is toluene diisocyanate.
2. The thermally conductive adhesive for a high thermally conductive double-sided tape according to claim 1, characterized in that: The hydroxy heterocyclic pyrrole is prepared by the reaction of amino acid methyl ester, carboxyl benzylmercapto oxadiazole and sodium methoxide.
3. The thermally conductive adhesive for a high thermally conductive double-sided tape according to claim 1, characterized in that: The carboxylbenzylmercaptooxadiazole is prepared by reacting 2-pyridinecarboxylic acid hydrazide, carbon disulfide and m-bromomethylbenzoic acid.
4. The thermally conductive adhesive for a high thermally conductive double-sided tape according to claim 1, characterized in that: The diamine nitrile rubber is prepared by reacting pentadecylphenol, decanediamine and polyformaldehyde to generate oxazine resin, which is then reacted with nitrile rubber.
5. A method for preparing a thermally conductive adhesive for a high thermally conductive double-sided tape as claimed in claim 1, characterized in that: The specific steps include: S1. 2-pyridinecarboxylic acid hydrazide, potassium hydroxide and methanol are mixed in a mass ratio of 7 to 8:5:100, stirred evenly and transferred to an ice bath, carbon disulfide of the same mass as 2-pyridinecarboxylic acid hydrazide is added dropwise at a rate of 1 to 3 ml / min, the temperature is raised to 60 to 70°C, the reaction is carried out for 3 to 6 hours, the mixture is rotary evaporated and dissolved in deionized water, the pH is adjusted to 4.8 to 5.2 with glacial acetic acid, and potassium hydroxide of 2 to 3 times the mass of 2-pyridinecarboxylic acid hydrazide and potassium hydroxide of the same mass as 2-pyridinecarboxylic acid hydrazide are added after filtration, and m-bromomethylbenzoic acid of 0.15 to 0.19 times the mass of 2-pyridinecarboxylic acid hydrazide is added after stirring evenly, the reaction is carried out at 400 to 800 rpm for 6 to 8 hours, the mixture is distilled under reduced pressure and the pH is adjusted to 2.8 to 3.2 with hydrochloric acid, the mixture is filtered and dried to obtain carboxybenzylmercaptooxadiazole; S2. The hydroxyheterocyclic pyrrole body and methanol are mixed in a mass ratio of 1 to 3:20, stirred evenly, and a 20 to 30% sodium methoxide solution of 1 to 3 times the mass of the hydroxyheterocyclic pyrrole body is added, the temperature is raised to 70 to 80 ° C, refluxed for 8 to 10 hours, cooled to room temperature, and then rotary evaporated and adjusted to pH 2 to 3 with hydrochloric acid, and chromatographed by a 2:1 volume ratio of ether alcohol and polyethylene column to obtain hydroxyheterocyclic pyrrole; S3. Mix hydroxyheterocyclic pyrrole and polyether polyol in a mass ratio of 1 to 3:40, heat to 100 to 110° C., vacuum dehydrate to a moisture content of 0.02 to 0.05%, cool to 40 to 50° C., add dibutyltin dilaurate in an amount of 0.01 to 0.02 times the mass of hydroxyheterocyclic pyrrole and polymethylene isocyanate in an amount of 1.4 to 1.8 times the mass of hydroxyheterocyclic pyrrole, heat to 75 to 85° C., keep warm for 4 to 6 hours, then add triethanolamine in an amount of 0.2 to 0.3 times the mass of hydroxyheterocyclic pyrrole, stir at 600 to 800 rpm for 20 to 40 minutes, and vacuum degas to obtain a modified polyurethane; S4. Put the nitrile rubber into a double-roll mill, add plasticizer DOP, stearic acid, paraffin and oxazine resin for mixing at a temperature of 40 to 60 ° C, add accelerator TMTD after 3 to 5 minutes, continue mixing for 10 to 20 minutes, take out and let stand for 24 hours, and then place it in an extruder base granulation to obtain diamine nitrile rubber; S5. Mix the modified polyurethane, diamine nitrile rubber, acrylate and curing agent toluene diisocyanate, raise the temperature to 180-220° C., stir evenly and react for 2-6 hours to obtain a thermally conductive adhesive for a high thermally conductive double-sided tape.
6. The method for preparing a thermally conductive adhesive for a high thermally conductive double-sided tape according to claim 5, characterized in that: In the above step S1., the preparation method of m-bromomethylbenzoic acid is: m-methylbenzoic acid, N-bromosuccinimide, benzoyl peroxide and carbon tetrachloride are mixed in a mass ratio of 10-13:18:0.2:150, refluxed for 6-8 hours, filtered and washed with carbon tetrachloride and deionized water for 3-5 times in sequence, and dried to obtain m-bromomethylbenzoic acid.
7. The method for preparing a thermally conductive adhesive for a high thermally conductive double-sided tape according to claim 5, characterized in that: In the above step S2., the preparation method of the hydroxyheterocyclic pyrrole blank is as follows: amino acid methyl ester, dichloromethane, 4-dimethylaminopyridine and EDC·HCl are mixed in a mass ratio of 0.1:3:0.18~0.2:0.28~0.3, and after stirring evenly, a dichloromethane solution of 2,4-dichlorophenylacetic acid with a mass fraction of 8~10% and a mass fraction of 20~30 times the mass of amino acid methyl ester is added dropwise at a rate of 1~3 ml / min, and after reacting for 16~20 hours, it is washed with a sodium bicarbonate solution with a mass fraction of 5% and deionized water for 3~5 times in sequence, dried with anhydrous sodium sulfate, filtered and concentrated to obtain a hydroxyheterocyclic pyrrole blank.
8. The method for preparing a thermally conductive adhesive for a high thermally conductive double-sided tape according to claim 5, characterized in that: In the above step S4., the preparation method of the oxazine resin is: 0.4 to 0.5 times the mass of decanediamine of the m-pentadecylphenol is added dropwise to the m-pentadecylphenol at a rate of 1 to 3 ml / min, and then the mass of paraformaldehyde of the m-pentadecylphenol is added, the temperature is raised to 90 to 95° C., and after reacting for 2 to 4 hours, the temperature is lowered to 70 to 75° C., the liquid is separated with deionized water and washed 3 to 5 times, and vacuum dried to obtain the oxazine resin.
9. The method for preparing a thermally conductive adhesive for a high thermally conductive double-sided tape according to claim 5, characterized in that: In the above step S4., the mass ratio of nitrile rubber, plasticizer DOP, stearic acid, paraffin and oxazine resin is 100:10:1.2:1.2:4-7.
10. The method for preparing a thermally conductive adhesive for a high thermally conductive double-sided tape according to claim 5, characterized in that: In the above step S1., the mass ratio of modified polyurethane, diamine nitrile rubber, acrylate and curing agent toluene diisocyanate is 20-40:8-9:30-50:3.